The effect of chicory (Cichorium intybus) and sulla (Hedysarum coronarium) on larval development and mucosal cell responses of growing lambs challenged with Teladorsagia circumcincta - Tzamaloukas, Ouranios; Athanasiadou, Spiridoula; Kyriazakis, Ilias (My University, 2006)
The aim of this study was to investigate the effects of grazing different bioactive forages on acquired immunity against Teladorsagia circumcinta infection. The development of immunity was assessed by following the response of trickle-infected lambs grazing chicory (Cichorium intybus; IC), sulla (Hedysarum coronarium; IS) or grass/clover (Lolium perenne/ Trifolium repens; IGC), to a single challenge infection. Parasite-naive lambs, grazing grass/clover, were also challenged with the single infection dose providing the uninfected control (UGC) group. Trickle infection significantly reduced worm establishment, inhibited larval development and increased mucosal mast cell (MMC) and globule leucocyte (GL) cells. Grazing treatment (chicory, sulla or grass/clover) significantly affected adult worm (P < 0.05), late-L4 (P < 0.01) and mid-L4 (P < 0.01) larval-stage recoveries of the trickle-infected lambs, with IGC group always carrying higher worm burdens than either IC or IS lambs. MMC and GL cells of trickle-infected lambs were positively correlated with the proportion of early-L4 worms recovered and negatively correlated with both the proportion of adult worms recovered and the total worm establishment, suggesting that the observed effects were due to an enhanced immune response. The results suggest elevated immune responses against T. circumcincta infections in growing lambs grazing on either sulla or chicory compared to those grazing on grass/clover, probably due to differences in forage nutritional values
Keywords: Chicory; Immunity; Sheep; Animal experimentation; Lambs; Cells; Biomass; Diet